RELASI ANTARA MENANTU PEREMPUAN DAN MERTUA PEREMPUAN DALAM BINGKAI FEMINISME DI ISTRI UNTUK PUTRAKU KARYA ALI GHALEM - Anna Sriastuti (Universitas Stikubank (UNISBANK) Semarang, 2010)
This study analyzes the relationship between mother in-law and daughter in-law in Ali Ghalem’s Istri Untuk Putraku in feminism frame. A series of analysis is done to find out the final shot of the study; the mother-daughter’s in-law relationship; proceeded by describing the characterization of the two main characters, and then finding out the conflicts happened between them, the actions against patriarchy done by the daughter in law which means actions against tradition and social society construction/norms stirred by patriarchal roles and finally ended by revealing the relationship between the two main female characters in the novel. In addition the this study, the writer’s purpose of writing this story will be covered to enrich the understanding of the conflicts, which lead to the tense relationship between mother in-law and daughter in-law. Key words: characterizations, conflicts, patriarchy